Expressive Textile Arts and Fashion-based Intervention for Youth with Emotional Distress: A Pilot Study (Global Journal of Human-Social Science, 2023)
Recent years have seen increased interest in early intervention in and prevention of mental health difficulties during adolescence In this pilot study a structured expressive textile art and fashion based ETAFB intervention was conducted to evaluate the beneficial effects on personal wellbeing and social interaction of youth with emotional distress A one-group pretest-posttest pilot study was conducted among 18 youth with emotional distress All the participants attended four sessions of ETAFB intervention All the participants were subjected to a preintervention test and a 4-week postintervention test using the Personal Wellbeing Index School Children PWI-SC 12-item General Health Questionnaire GHQ-12 and Social Interaction Anxiety Scale SIAS The study findings revealed that the ETAFB intervention was associated with significant improvements in some of the measurements This information provides the groundwork for a further study to investigate the effect of the ETAFB intervention on the relationship between youth well-being and facilitators
Keywords: textile art–based intervention; youth; emotional distress; personal well-being; fashion; general health